2016
DOI: 10.1038/ncomms10966
|View full text |Cite
|
Sign up to set email alerts
|

Cajal bodies are linked to genome conformation

Abstract: The mechanisms underlying nuclear body (NB) formation and their contribution to genome function are unknown. Here we examined the non-random positioning of Cajal bodies (CBs), major NBs involved in spliceosomal snRNP assembly and their role in genome organization. CBs are predominantly located at the periphery of chromosome territories at a multi-chromosome interface. Genome-wide chromosome conformation capture analysis (4C-seq) using CB-interacting loci revealed that CB-associated regions are enriched with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
170
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(188 citation statements)
references
References 74 publications
(91 reference statements)
13
170
0
3
Order By: Relevance
“…90,91,95,100 Cajal bodies consistently associate with specific loci on multiple chromosomes, many of which include snRNA gene arrays, snoRNAs, as well as other small U RNA and histone gene clusters. 11,12,[118][119][120] Following siRNA knockdown of essential Cajal body components, WDR79/WRAP53 or USPL1, these chromosomal regions were no longer clustered, and the expression of many of the associated small U RNA loci were significantly reduced. Thus, disruption of Cajal bodies leads to a loss of genome conformation and this may lead to inefficient expression of snRNAs.…”
Section: Smn and Cajal Body Structurementioning
confidence: 99%
“…90,91,95,100 Cajal bodies consistently associate with specific loci on multiple chromosomes, many of which include snRNA gene arrays, snoRNAs, as well as other small U RNA and histone gene clusters. 11,12,[118][119][120] Following siRNA knockdown of essential Cajal body components, WDR79/WRAP53 or USPL1, these chromosomal regions were no longer clustered, and the expression of many of the associated small U RNA loci were significantly reduced. Thus, disruption of Cajal bodies leads to a loss of genome conformation and this may lead to inefficient expression of snRNAs.…”
Section: Smn and Cajal Body Structurementioning
confidence: 99%
“…Intriguingly, several sequencing-based studies have recently indicated that NBs assemble as a direct consequence of specific gene expression activity and form characteristic long-lived contact interactions with a defined cohort of genomic loci and CTs. [19][20][21] Nonetheless, the limitations of these populationbased studies using millions of mostly asynchronous cells are becoming apparent. Despite indications that genomic domains are known to form and maintain numerous spatial associations with both near (kBp) and distant (MBp) genomic locations, 22 it is unknown how many physical gene pairing events occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Great strides have been made in the realm of high-content DNA FISH microscopy approaches (hiFISH), which utilize automated image acquisition and analysis tools to interrogate DNA probe libraries. 21,29,30 Potentially, this approach can accurately quantify gene pairing events that occur across larger linear genomic distances and between chromosomes at high-resolution but current highcontent microscopy experiments are still limited to only 4 distinct fluorophores for visualization (one of which must be dedicated to a nuclear stain for automated image analysis). Therefore, current methods are inadequate for the co-visualization of multiple genes in conjunction with co-detection of chromosome territories, sub-nuclear structures and/ or distinct epigenetic marks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations